Auxin is a central player in the hormone cross‐talks that control adventitious rooting. Issue 1 (12th March 2014) - Pacurar, Daniel Ioan; Perrone, Irene; Bellini, Catherine
<x xml:space="preserve">Abstract</x> Vegetative propagation of economically important woody, horticultural and agricultural species rely on an efficient adventitious root (AR) formation. The formation of ARs is a complex genetic trait regulated by the interaction of environmental and endogenous factors among which the phytohormone auxin plays an essential role. This article summarizes the current knowledge related to the intricate network through which auxin controls adventitious rooting. How auxin and recently identified auxin‐related compounds affect AR formation in different plant species is discussed. Particular attention is addressed to illustrate how auxin has a central role in the hormone cross‐talk leading to AR development. In parallel, we describe the molecular players involved in the control of auxin homeostasis, transport and signaling, for a better understanding of the auxin action during adventitious rooting.